The extent of citizens' knowledge of preservatives and their health effects - H. Obaid, Zhraa; S. Alhasan, Huda; AlKhawaldeh, Ahmad (International Journal of Psychosocial Rehabilitation, 2024)
Food technology has witnessed remarkable progress during the past decades through themanufacture of various types of food additives, which are estimated at 2500 types added to foodto become better specifications in terms of: nutritional value, color, flavor and stability, so it isvery important to know the effect of preservatives that are added to food during conservationoperations Without damage for a temporary or permanent period. This study aims to identifypreservatives (their uses and risks) from the consumer point of view and to verify the extent ofcitizens' knowledge of the basic variables related to the acceptance of food additives. To achievethe goals of the study, an electronic questionnaire consisting of more than (60) questions wasdownloaded across all social media, the site of the University of Babylon and the College ofBasic Education, with the participation of (105) people. The questionnaire included nine axesconsisting of: general information about preservatives and their types, industrial preservatives,how to preserve food, its harms, alternatives, pharmaceutical preservatives, preservatives injuices and finally barbic acid. The SPSS program was used to statistically analyze thequestionnaire data. The results showed that the cognitive assessment of preservatives byparticipants was average based on the values of the standard deviation and the mean of themean (0.421 -1.615) and (1.25- 3.05), respectively, as well as the values of the standarddeviation The mean of harm to the use of preservatives in food was recorded: (0.925), (1.69),which indicates that the mean cognitive level of people participating in the questionnaire.Thevalue of the significance level (α ≤0.05) showed that there were no statistical differences aboutthe opinions of participants on the importance or lack of preservatives, and therefore thecitizens' awareness about the use of preservatives in food falls on individuals and relevant  government institutions, as well as intensifying studies and research that show the facts of useAll preservatives in all foods